The Effect of Price And Service Quality on Customer Satisfaction - Edward Alexandro Lumbanraja; Riomas Sinurat; Vianta Romauli Situmeang (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the effect of price and service quality on customer satisfaction at Ayam Penyet Chintya. A quantitative approach was applied using a survey method, and data were collected through questionnaires distributed to consumers. The analysis was conducted using SPSS to explore the relationship among price, service quality, and customer satisfaction. The findings show that price has a positive and significant effect on customer satisfaction, indicating that fair and affordable prices can enhance consumers’ perceived value. Likewise, service quality also has a positive and significant impact on customer satisfaction, meaning that responsive, friendly, and reliable service contributes to a better dining experience. Furthermore, when combined, competitive pricing and excellent service quality jointly strengthen overall customer satisfaction. Therefore, culinary businesses should maintain price fairness and continuously improve service delivery to sustain customer loyalty and competitiveness in a dynamic market environment.